"A Little Bit of Light Dispels a Lot of Darkness": Online Disclosure of Child Sexual Abuse by Authority Figures in the Ultraorthodox Jewish Community in Israel. Issue 19 (October 2022) - Lusky-Weisrose, Efrat; Fleishman, Tzviki; Tener, Dafna
Social media sites such as Facebook have become popular platforms for promoting public awareness of sexual abuse by encouraging user engagement around this issue. There is, therefore, currently emerging research on the functions and implications of social media as a platform for sexual abuse disclosure. However, as yet, no study has examined this phenomenon specifically through a religious-cultural lens. This study explores perceptions of, barriers to, and motives underlying online disclosure of child sexual abuse (CSA) by religious authority figures (RAFs) in ultraorthodox Jewish society in Israel. The data were gleaned from the popular Facebook page of a nonprofit devoted to raising awareness of CSA in the ultraorthodox community. The analysis was based on admins' posts, anonymous and nonanonymous survivors' shares, users' comments, and in-depth interviews of eight page users. The findings suggest a culture-oriented model of online CSA disclosure (OCSAD), identifying four primary factors (safety, benefit, relevance, and legitimacy) that, weighed against cultural barriers, influence the decision to engage in online CSA disclosure. This context-informed understanding highlights the importance of social media as an alternative platform for CSA disclosure in an isolated but changing cultural arena such as the ultraorthodox community in Israel. The theoretical model is of international interest for its conceptualization of the unique characteristics and perceptions of OCSAD within religious-cultural contexts.